Faktor-Faktor Determinan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Mangasa - Simunati Simunati; Rosnah Rosnah; Suparta Mahmuddin (Celebes Advance Health Journal, 2025)
Background: Diarrhea in toddlers remains a public health problem in Indonesia, causing significant morbidity and mortality. Nutritional factors, sanitation, and maternal knowledge are often cited as the main determinants, but comprehensive studies in specific urban contexts such as the Mangasa Community Health Center are still limited. Objective: This study aims to identify the determinants of diarrhea in infants in the Mangasa Community Health Center working area, focusing on nutrition (exclusive breastfeeding), sanitation (clean water quality), and maternal knowledge levels. Method: A cross-sectional study design was used on 30 mother-infant pairs selected through purposive sampling. Data were collected through structured interviews using a valid questionnaire related to respondent characteristics, history of exclusive breastfeeding, clean water quality, and mothers' knowledge levels. Data analysis included descriptive and inferential statistics using the Chi-square test (p<0.05) with SPSS version 25. Results: Of the 30 toddlers, 9 (30%) had diarrhea. The majority of infants were aged >2–5 years (70%). A low history of exclusive breastfeeding was found in 17 infants (56.7%), use of unsuitable water in 11 respondents (36.7%), and insufficient maternal knowledge about diarrhea in 16 mothers (53.3%). Further analysis showed that these factors had a significant association with the incidence of diarrhea (p<0.05), indicating a pattern of mutually reinforcing risks. Conclusion: The incidence of diarrhea among toddlers at the Mangasa Community Health Center is greatly influenced by the interaction of nutrition (low exclusive breastfeeding), sanitation (poor quality of clean water), and lack of knowledge among mothers. Integrated educational interventions are needed to improve early detection and prevention of diarrhea.